Towards a Global Music History - Hijleh, Mark, author.
1 online resource (254 pages)
Keywords: How do we explain the globalized musical world in which we find ourselves in the early 21st century and how did we arrive here? This extraordinary book outlines an understanding of the human musical story as an intercultural—and ultimately a transcultural—one, with travel and trade as the primary conditions and catalysts for the ongoing development of musical styles. Starting with the cultural and civilizational precedents that gave rise to the first global trading and travel network in both directions across the Afro-Eurasian Old World Web in the form of the Silk Road, the book proceeds to the rise of al-Andalus and its influence on Europe through the Iberian peninsula before considering the fusion of European, African and indigenous musics that emerged in the Americas between c1500-1920 as part of Atlantic culture and the New World Web, as well as the concurrent acceleration of globalism in music through European empires and exoticism. The book concludes by examining the musical implications of our current Age of Instantaneous Exchange that technology permits, and by revisiting the question of interculturality and transculurality in music.